(untitled) (Kronika Bydgoska, 2021)
The article is a review of works carried out within the project “Digitalization of Academic Resources of the Region of Kuyavia and Pomerania for the needs of Science and Education of the Country.” Its goals included organization of access, popularization, protection and preservation for future generations valuable objects of culture and art in the collections of the UMK University Library, UKW University Library, Książnica Kopernikańska (Copernicus Library), the Museum of Diplomacy and Polish Refugees, and the Education Museum, as well as entering 15,000 online bibliographic book descriptions to UMK and UKW library catalogs, and through them – to the NUKAT central catalog. The UKW University Library digitized 10,000 documents in eight thematic collections: UKW Library Special Collections, Documents from Bydgoszcz Community Memorial Studio, Collection of the Department for Cultural Heritage of Eastern Borderlands, Archives of Wanda and Karol Poznański, Hungarian Collection, Collection of the Education Museum in Bydgoszcz, Reports of scientific societies and grammar schools in the 19th and 20th centuries from Książnica Kopernikańska, Repository of the Kazimierz Wielki University In 2018-2021, the UKW University Library in Bydgoszcz participated in implementation of the project “Digitalization of Academic Resources of the Region of Kuyavia and Pomerania for the needs of Science and Education of the Country.” Its beneficiary was the Nicolaus Copernicus University in Toruń. The project was financed by European Union funds (about Zl 3.9 million) and the state budget (almost Zl 707,000). The purpose of the project was organization of access, popularization, protection and preservation for future generations valuable objects of culture and art in the collections of the UMK University Library, UKW University Library, Książnica Kopernikańska (Copernicus Library), the Museum of Diplomacy and Polish Refugees, and the Education Museum, as well as entering 15,000 online bibliographic book descriptions to UMK and UKW library catalogs, and through them – to the NUKAT central catalog. As a result, the resources of the Kuyavian-Pomeranian Digital Library were expanded by 28,000 of objects that had never been digitized, and the UKW Repository received 1,800 new publications. Within the project, the UKW University Library digitized 10,000 documents held in eight thematic collections.